A texture-modified dessert with high nutritional value designed for people with dysphagia: effect of refrigeration and frozen storage - María Cartagena; Larisa Giura; Diana Ansorena; Iciar Astiasaran (Food Science and Human Wellness)
Dysphagia is commonly associated with malnutrition and an increased choking risk. To overcome these complications, food designed for people with dysphagia should have an appropriate texture and a high nutritional value. In this study, six formulations of a strawberry dessert enriched in protein (calcium caseinate) and fiber (wheat dextrin or inulin) were developed using different hydrocolloids (xanthan gum, carboxymethyl cellulose or modified starch) to provide desirable texture and stability. Nutritional value was calculated and total phenolic content and antioxidant activity of the samples were analyzed. Back-extrusion test, rheological measurements and sensory analysis were performed in refrigerated and frozen samples to characterize their textural and viscoelastic properties. The high content in protein (14.7 g/100 g) and fiber (7.98.7 g/100 g) made possible to use the claims “high protein” and “high fiber”. Phytochemicals supplied by strawberries contributed to the antioxidant properties of the dessert. Loss tangent ranged 0.280.35 for all the formulations, indicating a weak gel behavior, which could be considered safe to swallow. The formulations with dextrin in combination with carboxymethyl cellulose or xanthan gum seemed to be less susceptible to structural changes during frozen storage. This work provides insights for the development of a nutrient-dense dessert that meets the requirements of people with dysphagia.